(untitled) (Conferencea, 2023)
This article examines the concept of the language game, presented by Ludwig Wittgenstein. The author explains that language is a means of communication and expression of thoughts, and the exchange of ideas is possible only through language. The concept of a language game explains how language is used in practice and helps to understand its meaning and use in various situations. The study of the role and significance of language games opens the way for studying the relationship between language play and innovative thinking. The author also draws attention to the free use of linguistic elements and the emergence of wordplay and pluralism of meanings within the framework of the language game.